2006
DOI: 10.1021/ma052492b
|View full text |Cite
|
Sign up to set email alerts
|

Living Coordination Polymerization of Allene Derivatives in Protic Solvents:  Remarkable Acceleration of Polymerization and Increase of 1,2-Polymerization Selectivity

Abstract: The allylnickel-catalyzed living coordination polymerization of allene derivatives was carried out in protic solvents such as EtOH to figure out their effect on the polymerization behavior. For example, the coordination polymerization of methoxyallene (2a) by [(allyl)NiOCOCF3]2 (1)/PPh3 in EtOH proved to proceed in a living fashion giving a narrowly dispersed polymer in a high yield. In this case, a remarkable acceleration of the polymerization and the higher selectivity of the 1,2-polymerization were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…The polymer yield in solvent polymerization is lower than that in bulk, and the yield of polymerization in polar solvent is even lower. It was interesting to find that in contrast to the previously work, 7 the M w and yield of polymers increase with the solvent polarity. However, the polymer obtained in THF shows lower M w Table 1).…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…The polymer yield in solvent polymerization is lower than that in bulk, and the yield of polymerization in polar solvent is even lower. It was interesting to find that in contrast to the previously work, 7 the M w and yield of polymers increase with the solvent polarity. However, the polymer obtained in THF shows lower M w Table 1).…”
Section: Resultscontrasting
confidence: 57%
“…This result was consistent with the previous report. 7 Figure 7. It can be concluded that the apparent polymerization rate is first-order with respect to the concentration of n-octylallene.…”
Section: Scheme 1 Polymerization Of N-octylallene With Y(p 204 ) 3 / mentioning
confidence: 99%
See 1 more Smart Citation
“…In the laboratory of the coauthors, the allylnickel‐catalyzed living polymerization of allene derivatives has been studied, in which a wide variety of allene monomers including both nonpolar and polar functional groups can be polymerized in a living mechanism in both polar and non‐polar polymerization media . In addition, this living polymerization can be applied to the synthesis of copolymers of plural allenes, and allenes with other monomers such as butadiene and isocyanides .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this living polymerization can be applied to monomers bearing diverse functional groups such as alkyl, aryl, alkoxy, carboalkoxy, hydroxy and amide to produce welldefined polymers bearing the corresponding functional groups. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Additionally, this living polymerization can be carried out in protic polar media such as alcohols without any deactivations of the growing species. 47 In this paper, we describe the results of the π-allylnickelcatalyzed living dispersion polymerization of allene derivatives that enables the precision synthesis of well-defined polymer microspheres.…”
mentioning
confidence: 99%